Kajian Aspek Kultural Semar Pagulingan - I Ketut Yasa (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2008)
Ever since the spread of Semar Pagulingan to the countryside in Bali (out of the palace walls), it has experienced a significan change in form and function. This change is supposedly caused by an existing influence from non-aesthetic factors such as politics, religion and social issues. On the other hand, this change is also unavoidable from the views and behaviours of the Semar Pagulingan artists who, only depend on one side which is only to stay alive. With this view and attitude of conservation, sometimes without the artist realizing it, the Semar Pagulingan loses its soul. Referring to this, this study expresses various factors which trigger the change of the form and funclion Semar PagulinanKeyword : Semar Pagulingan, change, factors